Short-term glucosamine infusion increases islet blood flow in anesthetized rats - Gao, Xiang (Landes Bioscience, 2013)
Impaired glucose tolerance and type 2 diabetes in rodents are associated with increased islet blood flow. If this is important for modulation of the endocrine function is at present unknown. We evaluated if glucosamine infusion, which induces peripheral insulin resistance and glucose intolerance, could be used to acutely increase islet blood flow. We infused anaesthetized Sprague-Dawley rats for 2 h with glucosamine (6 mg/kg body weight), in some cases followed by glucose administration. The former induced a 2-fold increase in serum insulin concentrations while plasma glucose remained unchanged. In vitro an augmented insulin response to hyperglycemia and decreased insulin content in batch type islet incubations with glucosamine for 24 h were seen. After 2 h glucosamine exposure in vitro, insulin release was decreased. In vivo glucosamine infusion increased islet blood flow, without affecting other regional blood flow values. Glucose increased islet blood flow to the same extent in control and glucosamine-infused rats. When exposed to 10 mmol/L glucosamine arterioles of isolated perfused islets showed a 10% dilation of their vascular smooth muscle. Thus, application of this model leads to acute hyperinsulinemia in vivo but a decreased insulin release in vitro, which suggests that effects not located to β cells are responsible for the effects seen in vivo. An increased islet blood flow in previously healthy animals was also seen after glucose administration, which can be used to further dissect the importance of blood flow changes in islet function.